The role of type VI secretion system genes in antibiotic resistance and virulence in Acinetobacter baumannii clinical isolates - Li, Pu; Zhang, Sirui; Wang, Jingdan; Al-Shamiri, Mona Mohamed; Luo, Kai; Liu, Shuyan; Mi, Peng; Wu, Xiaokang; Liu, Haiping; Tian, Huohuan; Han, Bei; Lei, Jin’e; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
The type VI secretion system (T6SS) is a crucial virulence factor in the nosocomial pathogen Acinetobacter baumannii. However, its association with drug resistance is less well known. Notably, the roles that different T6SS components play in the process of antimicrobial resistance, as well as in virulence, have not been systematically revealed. In this study, we investigated the importance of three representative T6SS core genes involved in the drug resistance and virulence of A. baumannii, namely, tssB, tssD (hcp), and tssM.A higher ratio of the three core genes was detected in drug-resistant strains than in susceptible strains among our 114 A. baumannii clinical isolates. To determine the effect of each core gene, we inactivated tssB, tssD, and tssM in AB795639. Upon deletion of tssB, increased antimicrobial resistance to cefuroxime and ceftriaxone was observed, alongside reduced resistance to gentamicin. The ΔtssD mutant showed decreased resistance to ciprofloxacin, norfloxacin, ofloxacin, tetracycline, and doxycycline, but increased resistance to tobramycin and streptomycin. The tssM-lacking mutant showed an increased sensitivity to ofloxacin, polymyxin B, and furazolidone. In addition, a significant reduction in biofilm formation was observed only with the ΔtssM mutant. Moreover, the ΔtssM strain, followed by the ΔtssD mutant, showed decreased survival in human serum, with attenuated competition with Escherichia coli and impaired lethality in Galleria mellonella. These results suggest that T6SS plays an important role, participating in the antibiotic resistance of A. baumannii, especially in terms of intrinsic resistance. Meanwhile, tssM and tssD contribute to bacterial virulence to a greater degree, with tssM being associated with greater importance.